Security attacks taxonomy on bring your own devices (BYOD) model - Singh, Manmeet Mahinderjit; Soh, Sin Siang; Oh, Ying San; Malim, Nurul Hashimah Ahamed Hassain; Shariff, Azizul Rahman Mohd (Wireilla, 2014)
Mobile devices, specifically smartphones, have become ubiquitous. For this reason, businesses are starting to develop “Bring Your Own Device” policies to allow their employees to use their owned devices in the workplace. BYOD offers many potential advantages: enhanced productivity, increased revenues, reduced mobile costs and IT efficiencies. However, due to emerging attacks and limitations on device resources, it is difficult to trust these devices with access to critical proprietary information. Therefore, in this paper, the potential attacks of BYOD and taxonomy of BYOD attacks are presented. Advanced persistent threat (APT) and malware attack are discussed in depth in this paper. Next, the proposed solution to mitigate the attacks of BYOD is discussed. Lastly, the evaluations of the proposed solutions based on the X. 800 security architecture are presented.